Trade and Agglomeration: the Strategic use of Protection Revisited - Susanna Thede (Lund University, School of Economics and Management, Department of Economics, 2007)
The purpose of this paper is to examine whether the strategic motive for protection present in trade and agglomeration models, in the so-called new economic geography framework, is sensitive to the standard assumption that there is a sole agglomeration industry. We first investigate unilateral trade policy effects on the international production and trade pattern and the resulting national welfare levels in a new economic geography model including several agglomeration industries. The strategic use of trade policy is then examined by identifying optimal policy positions as well as equilibrium policy strategies in a Nash policy game between the trade partners. Our results show that the strategic use of protection and the resulting "tariff war" outcome prevalent in standard trade and agglomeration models is sensitive to the inclusion of several agglomeration industries. Specifically, trade liberalising policies are optimal and free trade equilibria result from the Nash game unless there is a too wide industry gap in agglomeration economies. Our results show that the case for free trade can be directly attributed to either a relatively strong direct policy impact on national real income (working through raised import prices and reduced import volumes) or similar agglomeration economies in the two industries. The results of this paper jointly suggest that the stark argument for the strategic use of protection present in standard new economic geography models can be attributed to overemphasised gains from agglomeration and/or the lack of industries with similar agglomeration economies.
Keywords: F12; F13; R12; R13; 330; New economic geography; input-output linkages; strategic trade policy; Nash policy game.